(3LRA ajg ef MOjK GHf NPdes - (3CHh GdMSf CMeO Hf SdjeGf Hf GjhH Hf NPde GdbGVjs
(3ChdgG (B:s
(3GNHQfG GdTjN CHh eMeO YHO Gddg Hf GSO Hf YeGQ bQCg Ydjg HOGQg HeOjfI OeTb ai jhe GdLeYI NGeS YTQ QHjY GdGNQ ef SfI SJ hNeSjf hNeSeGFI s
(3BNQgG (B:s
(3MOKfG jRjO bGd MOKfG gTGe Hf GSeGYjd bGd MOKfG GHf TeGYI Yf GdGhRGYi bGd MOKfi YHOg Hf CHj dHGHg bGd MOKfi fGaY ehdi GHf YeQ bGd cGf YHO Gddg Hf YeQ jUdi Ydi XgQ QGMdJg Je GdLRA hGdMeO ddg cKjQkG s
(3GdfSNI HgG MhGTs
(3SeGY YHO Gddg Hf YjSi Hf YHjO Gddg Hf YjSi GdeQGOi GdGfOdSis
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQI GdYfhGf (B:s
(3LeY s
Keywords: (3GdMOjK h GdeUWdMs